The 5-HT7 receptor as a potential target for treating drug and alcohol abuse - Hauser, Sheketha R.; Hedlund, Peter B.; Roberts, Amanda J.; Sari, Youssef; Bell, Richard L.; Engleman, Eric A. (Frontiers in Neuroscience, 2015)
Alcohol and drug abuse take a large toll on society and affected individuals. However, very few effective treatments are currently available to treat alcohol and drug addiction. Basic and clinical research has begun to provide some insights into the underlying neurobiological systems involved in the addiction process. Several neurotransmitter pathways have been implicated and distinct reward neurocircuitry have been proposed – including the mesocorticolimbic (MCL) dopamine system and the extended amygdala. The serotonin (5-HT) neurotransmitter system is of particular interest and multiple 5-HT receptors are thought to play significant roles in alcohol and drug self-administration and the development of drug dependence. Among the 5-HT receptors, the 5-HT-7 receptor is currently undergoing characterization as a potential target for the treatment of several psychiatric disorders. Although this receptor has received only limited research regarding addictive behaviors, aspects of its neuroanatomical, biochemical, physiological, pharmacological, and behavioral profiles suggest that it could play a key role in the addiction process. For instance, genomic studies in humans have suggested a link between variants in the gene encoding the 5-HT-7 receptor and alcoholism. Recent behavioral testing using high-affinity antagonists in mice and preliminary tests with alcohol-preferring rats suggest that this receptor could mediate alcohol consumption and/or reinforcement and play a role in seeking/craving behavior. Interest in the development of new and more selective pharmacological agents for this receptor will aid in examining the 5-HT-7 receptor as a novel target for treating addiction.